A Rare Case of Partial Aortic Mechanical Valve Thrombosis With Intact Mitral Mechanical Valve Presenting With ST-Elevation Myocardial Infarction Patients. (October 2020) - Khalid, Mazin O.; Malyshev, Yury; Hashmi, Arsalan Talib; Siddiqui, Sabah; Patel, NeelKumar; Shani, Jacob; Ayzenberg, Sergey
The incidence of mechanical valve thrombosis (MVT) is around 0.4 per 100 patient-years. Mitral valve thrombosis has a higher incidence than aortic valve thrombosis with a nearly 5-fold increase. Various factors contribute to MVT. The most common cause of valve thrombosis is poor adherence/disruption of anticoagulation therapy. Low cardiac output is known to increase the risk of prosthetic valve thrombosis. Other factors such as diabetes, hypertension, and other patient comorbidities might also play a role. Decreased flow promotes hypercoagulability. Lower pressure in the left atrium (and higher velocities in the left ventricle) can partially contribute to the higher incidence of mitral MVT versus aortic MVT. The presenting symptoms usually depend on the severity of the valve thrombosis; nonobstructive valve thrombosis patients have progressive dyspnea, signs of heart failure, and systemic embolization with strokes being the most common complication. In this article, we present a case of a middle-aged woman with a history of mitral and aortic mechanical prosthesis who presented with an ST-segment elevation myocardial infarction and pulmonary edema due to mechanical aortic valve prosthesis thrombosis. She had an isolated mechanical aortic valve prosthesis thrombosis with intact mitral valve, which, to the best of our knowledge, has not yet been described. We performed a literature review by searching PubMed and Embase using the keywords "mechanical valve, " "thrombosis, " "aortic, " and "mitral, " our search did not show similar cases.